Optimizing treatment outcomes: immune tolerance induction in Pompe disease patients undergoing enzyme replacement therapy - Chen, Hui-An; Hsu, Rai-Hseng; Fang, Ching-Ya; Desai, Ankit K.; Lee, Ni-Chung; Hwu, Wuh-Liang; Tsai, Fuu-Jen; Kishnani, Priya S.; Chien, Yin-Hsiu (Frontiers in Immunology, 2024)
Introduction Pompe disease, a lysosomal storage disorder, is characterized by acid α-glucosidase (GAA) deficiency and categorized into two main subtypes: infantile-onset Pompe disease (IOPD) and late-onset Pompe disease (LOPD). The primary treatment, enzyme replacement therapy (ERT) with recombinant human GAA (rhGAA), faces challenges due to immunogenic responses, including the production of antidrug antibody (ADA), which can diminish therapeutic efficacy. This study aims to assess the effectiveness of immune tolerance induction (ITI) therapy in cross-reactive immunologic material (CRIM)-positive Pompe disease patients with established high ADA levels.Method In a single-center, open-label prospective study, we assessed ITI therapy's efficacy in Pompe disease patients, both IOPD and LOPD, with persistently elevated ADA titers (≥1:12,800) and clinical decline. The ITI regimen comprised bortezomib, rituximab, methotrexate, and intravenous immunoglobulin. Biochemical data, biomarkers, ADA titers, immune status, and respiratory and motor function were monitored over six months before and after ITI.This study enrolled eight patients (5 IOPD and 3 LOPD). After a 6-month ITI course, median ADA titers significantly decreased from 1:12,800 (range 1:12,800-1:51,200) to 1:1,600 (range 1:400-1:12,800), with sustained immune tolerance persisting up to 4.5 years in some cases. Serum CK levels were mostly stable or decreased, stable urinary glucose tetrasaccharide levels were maintained in four patients, and no notable deterioration in respiratory or ambulatory status was noted. Adverse events included two treatable infection episodes and transient symptoms like numbness and diarrhea.Conclusion ITI therapy effectively reduces ADA levels in CRIM-positive Pompe disease patients with established high ADA titers, underscoring the importance of ADA monitoring and timely ITI initiation. The findings advocate for personalized immunogenicity risk assessments to enhance clinical outcomes. In some cases, prolonged immune suppression may be necessary, highlighting the need for further studies to optimize ITI strategies for Pompe disease treatment. ClinicalTrials.gov NCT02525172; https://clinicaltrials.gov/study/NCT02525172 No: number, AEs: adverse events, TEAEs: treatment emergent adverse events